Pengaruh Pendidikan Kewirausahaan Terhadap Kompetensi Usaha Rintisan Dalam Pemberdayaan Calon Penata Rias - Saripah, lip; Suryadi, Ace; Sardin, Sardin; Lestari, Retno Dwi (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2024)
This research aims to analyze the influence of entrepreneurship education on startup business competencies through the empowerment of prospective makeup artists. The study employs a quantitative approach with structural equation model analysis techniques using the AMOS application. The population of this study comprises alumni of the Entrepreneurial Skills Education Program (PKW) from Training and Course Institutes (LKP) between 2016 and 2018 in West Java. The sampling technique used is random sampling. Data were obtained through a questionnaire completed by 136 respondents. The results of the study indicate that entrepreneurship education does not have a significant effect on startup business competencies through the empowerment of prospective makeup artists. However, entrepreneurship education significantly influences two variables: startup business competencies (48.6%) and the empowerment of prospective makeup artists (89.1%). The study reveals the reasons for the low achievement of the PKW Program's success based on two indicators. Indicator II states that at least 75% of graduates should be able to start a business, and Indicator III specifies that at least 30% of those who start a business should earn an income equivalent to the local minimum wage within six months. The low success rate of the PKW Program in this study is explained by the limited skills of the mentors and the lack of reflection activities during the mentoring process. This research highlights the urgent need for effective mentors when prospective bridal makeup artists design and launch their startups. Mentors play a critical role in providing business insights, market advice, and market validation. Therefore, it is necessary to improve the quality of mentors and establish qualification standards for startup business mentors.